A new tool to attack biofilms: driving magnetic iron-oxide nanoparticles to disrupt the matrix. Issue 14 (26th March 2019) - Li, Jie; Nickel, Rachel; Wu, Jiandong; Lin, Francis; van Lierop, Johan; Liu, Song
Abstract : Removing robust MRSA biofilms using magnetic nanoparticles (MNPs) under AC and DC magnetic field is demonstrated. Despite being non-toxic to planktonic bacteria, MNPs can bring damage to the extracellular matrix of biofilms and remove them from surfaces without inducing bacterial resistance. Abstract : A main feature of biofilms is the self-produced extracellular polymeric substances (EPSs) that act as a protective shield, preventing biocide penetration. We use magnetic iron oxide nanoparticles (MNPs) in combination with magnetic fields to damage the biofilm matrix and cause detachment. A Methicillin-resistant Staphylococcus aureus (MRSA) biofilm strain is used to demonstrate the efficacy of the methodology with different sizes and concentrations of MNPs under AC and DC applied field conditions. We achieve up to a nearly 5 log10 reduction in biofilm bacteria after treatment with 30 mg mL −1 of 11 nm MNPs using a magnetic field. The MNPs cause significant mechanical disruption to the matrix and lead to biofilm dispersal. In addition, using magnetic hyperthermia further affects biofilm damage.